Validation of simplified tying force method for robustness assessment of RC framed structures. (15th December 2021) - Ravasini, S.; Sio, J.; Franceschini, L.; Izzuddin, B.A.; Belletti, B.
Highlights: Validation of a new simplified rational tying force method for the robustness/progressive collapse assessment of reinforced concrete systems. Simplified tying method to reproduce catenary/membrane phase of reinforced concrete systems explicitly considering rotational ductility. Comparison between experimental results and simplified tying force to establish the representative level of rotational ductility. Suitability of the simplified tying force method as a robustness assessment framework for reinforced concrete structures for the next generation of Eurocodes. Abstract: The robustness of reinforced concrete (RC) structures is an important ongoing research topic in the civil engineering community. Especially in the last decades, the need for structural robustness assessment methods has become urgent, and several design methods have been proposed in codes and guidelines to mitigate the progressive collapse risk of reinforced concrete structures. The most used approaches are the Tying Force and Alternate Load Path methods. The first is typically applied as an indirect and prescriptive method where the building is considered mechanically tied together and able to enhance continuity and the resistance to progressive collapse. The second is a direct method, where the capacity of the structure to sustain the applied loads is evaluated after the loss of a load-bearing element, most effectively using advanced nonlinear structural analysis methods. In the context of the Tying Force method, the Eurocode is recognised to underestimate the tie force demands required by building structures subject to the loss of a load bearing member, which are better reflected in the USA UFC Guidelines. A new Tying Force method has been proposed by Izzuddin & Sio (2021) for the next generation of the Eurocodes, which addresses the shortcomings of the present Eurocode guidance, and provides a more comprehensive treatment than considered in the UFC code. The present paper is aimed specifically at the validation of the new Simplified Tying Force method (Izzuddin & Sio, 2021) for reinforced concrete structures, considering grillage and combined beam/slab floor systems, and considering the rotational ductility of such structures, which is explicitly considered in the new method.